المقاولاتية النسائية في بعض الدول العربية- الجزائر، الأردن ولبنان نموذجا- (Journal of Economics and Management Research, 2020)
هدفت هذه الدراسة إلى التعرف على المقاولاتية النسائية في كل من الجزائر، الأردن ولبنان حيث عرفت الدول العربية اهتماما كبيرا بالمرأة وبالدور الفعال الذي تمارسه على مستوى الحياة الثقافية، الاجتماعية والاقتصادية، ويعود ذلك إلى النجاح الذي تمكنت المرأة من تحقيقه في تسيير مشاريعها الخاصة وتفوقها في ممارسة العمل المقاولاتي، وهذا ما دفع العديد من الدول العربية إلى العمل على تفعيل دور المرأة في العمل المقاولاتي وذلك من خلال وضع السياسات الهادفة والإجراءات المساندة على تذليل الصعوبات التي تواجه المقاولاتية النسوية. وقد توصلت الدراسة إلى أن هناك توجه للمرأة نحو العمل المقاولاتي حيث أن المقاولاتية النسائية تعتمد بشكل كبير على أجهزة الدعم في الجزائر، كما أن لبنان استطاعت التفوق على الأردن من حيث معدل النوايا الريادية للمرأة. Abstract: This study aimed to identify the reality of women's entrepreneurship in Algeria, Jordan and Lebanon, where the Arabic countries knew great caring for women and the effective role they play in the level of cultural, social and economic life, due to the success that women were able to achieve in the managing of their own projects and their superiority in The practice of entrepreneurial work, and this is what prompted many Arab countries to work to activate the role of women in entrepreneurial work through the development of Purposeful policies and supportive procedures to reduce the difficulties faced by women entrepreneurship. The study found that There is a tendency for women towards entrepreneurship, whereas women entrepreneurship relies heavily on Support devices in Algeria, and Lebanon was able to outperform Jordan in terms of the rate of women's entrepreneurial intentions.